Sentir o clima, aprender com a floresta e acessar o mundo: como a acessibilidade comunicativa pode contribuir para eliminar barreiras informativas do telejornalismo para pessoas com deficiência - (:unkn) unknown (Universidade Federal do Pampa, 2023)
The object of this research was the production processes of the TV Cultura program "Boas Práticas Escolares" (Good School Practices), analyzed in the light of the theory of mediations (Martín-Barbero, 2006) in relation to the issues of Communicative Accessibility (Bonito, 2015) and Communicative Citizenship (Mata, 2006). Although the Brazilian Inclusion Law (Lei Brasileira de Inclusão - LBI) and the Universal Declaration of Human Rights (Declaração Universal dos Direitos Humanos - DUDH) guarantee the right to information and communication for all people, regardless of their diversity, exploratory research identified a deficiency on the part of the majority of TV news media in implementing Communicative Accessibility as a practice in their production routines. Given this context, the research was based on the following problem: "How do the journalistic communication processes used in TV Cultura's telejournalism contribute to achieving the sustainable development goals of the 2030 Agenda, due to the inclusion and citizenship of people with disabilities in terms of Communicative Accessibility?". The choice of TV Cultura took into account the quality of the public telejournalism produced by the broadcaster (Silva, 2020) and the pioneering spirit with the creation of the Accessibility Center, called FLICTS. The methodology followed the exploratory research with a bibliographical review of the main works related to the topic; theoretical research and selection of reference works; and research to understand other methodological approaches to the subject. In-depth interviews (Duarte, 2005) were then carried out with journalists and professionals responsible for the accessibility of "Good School Practices". The results identified the difficulty of implementing Communicative Accessibility as part of journalistic narratives from pre-production to post-production, often caused by journalists' lack of technical knowledge on the subject. It was also possible to see that social sensitivity, which mediates technicality and production routines, together with cultural exchanges between professionals, are elements that enhance the practice of journalism with Communicative Accessibility that leads to the Communicative citizenship of people with disabilities.
Keywords: Comunicação; Projeto de acessibilidade; Telejornalismo; TV Cultura de São Paulo; Cidadania; Desenvolvimento Sustentável; Communication; Accessibility design; CNPQ::CIENCIAS SOCIAIS APLICADAS